Development of Biology Podcast-Based Learning Media (Bee O Podcast) on Environmental Change Material - Iwan Ridwan Yusup; Desi Widiya Astuti desi (CV. Generasi Intelektual Digital (GEN ID), 2025)
The digitisation of 21st-century learning media that knows no distance, time, or space, can be accessed anywhere and anytime, is rapidly developing to clarify the concept of lifelong learning. As a result, the quality of education increases, learning becomes effective, interesting, and innovative. This study aims to develop products and determine students’ responses to biology podcast learning media (Bee O Podcast) on environmental change material. The development of biology podcasts uses the Research and Development (R&D) research method of the 4D model from Thiagarajan, simplified to 3D (Define, Design, and Develop). The define stage is a preliminary study of biology learning through teacher interviews, analysis of student characteristics through survey questionnaires, and task-concept-objective analysis of learning environment change material in class X MIPA. The design stage is the preparation of research instruments, selection of media formats, and media design according to the analysis of the previous stage. At the development stage, the media were validated by experts and tested with 15 students. The results of the validity of biology podcasts from material experts were 87.50% (very valid), media experts 76.36% (valid), and biology teachers 84.21% (very valid). The average validity value of the biology podcast was 82.69% (very valid), and the students’ response to the biology podcast was 82.25% (very feasible). This shows that the biology podcast media product (Bee O Podcast) is feasible to use in learning environmental change material, especially environmental pollution material.